2003
DOI: 10.1038/sj.bjc.6600875
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 isoform b expression in human prostate cancer

Abstract: Overexpression of fibroblast growth factor 8 (FGF8) mRNA has been previously described in prostate cancer. Of its four isoforms, FGF8b is thought to be the most important in carcinogenesis. We hypothesised that immunodetection of FGF8b in archival prostate cancer specimens is of potential prognostic value. Using a selected cohort of prostate tumours from transurethral (n ¼ 30) and radical prostatectomies (n ¼ 59), an optimised protocol for FGF8b immunoreactivity was used to corroborate expression with clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 25 publications
1
68
0
Order By: Relevance
“…So it is notable that several changes in the FGF signaling axis have been described in prostate cancer (CaP) that can disrupt normal stromal-epithelial interactions (Kwabi-Addo et al, 2004). One such event is alternative mRNA splicing that generates the FGFR2IIIc isoform, which preferentially recognizes epithelial-derived FGF1, FGF2, FGF6 as well as FGF8, which is preferentially expressed in malignant prostate epithelium (Gnanapragasam et al, 2003). Alternate splicing of FGFRs and differential expression of FGF ligands can impart stromal independence on the epithelium by establishing autocrine growth factorsignaling loops.…”
mentioning
confidence: 99%
“…So it is notable that several changes in the FGF signaling axis have been described in prostate cancer (CaP) that can disrupt normal stromal-epithelial interactions (Kwabi-Addo et al, 2004). One such event is alternative mRNA splicing that generates the FGFR2IIIc isoform, which preferentially recognizes epithelial-derived FGF1, FGF2, FGF6 as well as FGF8, which is preferentially expressed in malignant prostate epithelium (Gnanapragasam et al, 2003). Alternate splicing of FGFRs and differential expression of FGF ligands can impart stromal independence on the epithelium by establishing autocrine growth factorsignaling loops.…”
mentioning
confidence: 99%
“…Consistent with these findings, it has been demonstrated that FGF8b overexpression in both prostate and breast cancer cells can promote tumor cell growth and formation in nude mice (Song et al, 2000;Ruohola et al, 2001), whereas specific downregulation of FGF8b by antisense RNA inhibited the in vivo tumorigenicity of prostate cancer cells (Rudra-Ganguly et al, 1998). These cumulative evidences establish the role of FGF8b in carcinogenesis of hormone-related cancers (Tanaka et al, 1998;Marsh et al, 1999;Gnanapragasam et al, 2003).…”
Section: Introductionmentioning
confidence: 66%
“…Further genomic and functional characterization of the FGF8 family demonstrated that the FGF8b isoform (one of the four human FGF8 isoforms: FGF8a, b, e and f (Gemel et al, 1996)) possesses the greatest mitogenic and, more importantly, the greatest transforming activity than the other isoforms, both in vitro and in vivo (MacArthur et al, 1995a(MacArthur et al, , 1995bBlunt et al, 1997;Song et al, 2000;Olsen et al, 2006). It is believed that FGF8b is one of the most important FGF8 isoforms in human carcinogenesis Gnanapragasam et al, 2003), although the exact physiological function of each isoform is yet-to-be fully revealed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations